Phonon dynamics of graphene on metals. (18th February 2016) - Al Taleb, Amjad; Farías, Daniel
Abstract: The study of surface phonon dispersion curves is motivated by the quest for a detailed understanding of the forces between the atoms at the surface and in the bulk. In the case of graphene, additional motivation comes from the fact that thermal conductivity is dominated by contributions from acoustic phonons, while optical phonon properties are essential to understand Raman spectra. In this article, we review recent progress made in the experimental determination of phonon dispersion curves of graphene grown on several single-crystal metal surfaces. The two main experimental techniques usually employed are high-resolution electron energy loss spectroscopy (HREELS) and inelastic helium atom scattering (HAS). The different dispersion branches provide a detailed insight into the graphene–substrate interaction. Softening of optical modes and signatures of the substrate′s Rayleigh wave are observed for strong graphene–substrate interactions, while acoustic phonon modes resemble those of free-standing graphene for weakly interacting systems. The latter allows determining the bending rigidity and the graphene–substrate coupling strength. A comparison between theory and experiment is discussed for several illustrative examples. Perspectives for future experiments are discussed.